PEMANFAATAN CHAT GPT OPEN AI TERHADAP ANALISIS DAN STRATEGI DALAM MENINGKATKAN PERFORMA PENJUALAN PRODUK SECARA DIGITAL - Julianto, Julianto (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
The rapid development of technology can produce several new innovations that are beneficial to society such as ChatGPT Open AI. ChatGPT is an artificial language model developed by OpenAI, an artificial intelligence technology company. GPT stands for